Techniques for essential oil extraction from kaffir lime and its application in health care products—A review. (22nd October 2020) - Suresh, Anuja; Velusamy, Sangeetha; Ayyasamy, Sudha; Rathinasamy, Menaha
Abstract: Kaffir lime ( Citrus hystrix DC) is a tropical plant with aromatic leaves. It produces fruits that are used in Asian cuisines as a flavoring agent. Essential oil from the leaves and peel of kaffir lime is a complex mixture of volatile and semi‐volatile compounds. It is rich in bioactive molecules that act synergistically to improve the well‐being of an individual. The method of extraction is important as it affects the quality and quantity of essential oil significantly. Kaffir lime oil is used as raw material in many fields, some of which include pharmaceutical, agronomic, food, sanitary, cosmetic, and perfume industries. It is also used extensively in aromatherapy and as an essential ingredient of various cosmetic and beauty products. Hydrodistillation, steam distillation, pressurized liquid extraction, and soxhlet extraction are some of the commonly used methods for extracting essential oil from kaffir lime as they are cost‐effective, environment friendly, and easy to implement on commercial scale. This review discusses about the condition's of extraction, merits, and demerits of various extraction methods used for kaffir lime oil and their application in healthcare products to induce positive effect in humans. Abstract : Different extraction methods for extracting essential oil from the leaf and peel of kaffir lime and its application in health care products is critically reviewed.